Geodemography: Geospatial Stream of Demographic Analysis - Gnyawali, Bishal; Sigdel, Uddhav (Janajyoti Journal, 2025)
Geo-demography, an emergent subfield at the intersection of geography and demography, integrates spatial technologies such as Geographic Information Systems (GIS), remote sensing, and spatial statistics to enhance the understanding of population dynamics within their spatial and socio-environmental contexts. This comprehensive review critically examines the theoretical foundations, methodological innovations, analytical techniques, and diverse applications of geo-demography in urban planning, public health, market segmentation, and disaster management, with a regional focus on South Asia. Employing a qualitative meta-synthesis approach and adhering to PRISMA guidelines, the study synthesizes 30 key scholarly works selected from global academic databases. It highlights how geo-demography contributes to spatially informed and equitable decision-making by revealing patterns in migration, urbanization, health disparities, and service accessibility. However, the review also identifies critical gaps, including inconsistent data quality, lack of methodological standardization, limited application in rural and low-income settings, and ethical concerns related to privacy and surveillance. It underscores the need for participatory approaches, interdisciplinary collaboration, and the integration of critical geographic perspectives to address spatial inequalities and demographic vulnerabilities. Looking ahead, the review advocates for the incorporation of Artificial Intelligence (AI), real-time data, and ethical data governance to expand the scope and impact of geo-demography in the Global South. Ultimately, the study positions geo-demography as a vital tool for sustainable development, digital governance, and inclusive policy-making in an increasingly spatially complex world.